Scalable HEVC for histological whole-slide image compression - Bug, Daniel; Bartsch, Felix; Schaadt, Nadine Sarah; Wien, Mathias; Feuerhake, Friedrich; Schüler, Julia; Oswald, Eva; Merhof, Dorit (Informatik aktuell, 2020)
Digital whole-slide images (WSI) are scanned representations of histological tissue at microscopic scale, enabling computer aided diagnosis and remote pathology applications. However, the data sizes may hinder a widespread use, as raw files can easily exceed 10-20GB. In this work, we explore the Scalable High Effciency Video Coding (SHVC) as a replacement for the JPEG standard currently found in most vendor formats. Besides a comparison of the compression rates, this work comprises a user-study to estimate SHVC quantization parameters (QP) and JPEG quality level that threshold the just-noticeable distortions (JND) for a compression below the JND.
CRIS-Team Scopus Importer:2023-03-23